EVALUASI PENDIDIKAN AGAMA ISLAM PADA SMP - Achmad Dudin (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2007)
AbstractIn order to improve the quality of education in Indonesia, Government has published Gov. Regulation Number 19 of 2005 on National Standard of Education (SNP). This SNP functioned as the basic fr planning, implementing and supervising of education, in order to realize a qualified national education. For having assurance and quality control of education implementation, evaluation is needed to be done-including to Islamic education (PAI). This research focused on evaluation of Islamic education process in 10 cities in Indonesia. Its result shows that Junior High Schools graduated in 2006/2007 period have reached a good achievment. Their report score was also categorized good, this indicated by a raising score on their odd and even semesters. These all are caused by input and process factors which closed to Standard of National Education.